The role of financial market development in foreign direct investment and foreign portfolio investment in selected African economies - Makoni, Patricia Lindelwa Rudo (My University, 2016)
The primary objective of this study was to investigate the role played by financial market development (FMD) in harnessing international capital flows of foreign direct investment (FDI) and foreign portfolio investment (FPI) in nine selected African economies, from 1980 to 2014. The study employed various econometric techniques such as the Generalised Method of Moments (GMM) for the dynamic panel data, Autoregressive Distributed Lag (ARDL) bounds testing approach to cointegration, Vector Error Correction Models (VECM) as well as Granger-causality tests. Using Principal Components Analysis (PCA), we also developed an infrastructural development index, as well as one for financial market development. The results highlighted that FDI to sampled African countries are determined by agglomeration effects, FPI, human capital development, real gross domestic product (GDP) growth, interest rates, inflation, infrastructure, trade openness, institutional quality, natural resources, and only certain individual financial market variables. FDI determinants are magnified by the application of the infrastructural and financial market development indices. FPI inflows, on the other hand, are influenced by FDI, exchange rates, stock market capitalisation, financial system liquidity, FPI agglomeration effects, capital account openness, and real GDP growth rates. The composite FMD index has a positive and highly significant effect on both FDI and FPI inflows to the selected African countries. There is reasonable evidence of bi-directional Granger causality between FDI and FPI, and FPI and overall FMD (FMD index), thus implying complementarity, as well as uni-directional Granger causality emanating from FDI to stock market capitalisation, FDI to domestic credit to the private sector by banks and also from FDI to overall financial market development in Botswana, Cote d’Ivoire, Egypt, Kenya, Mauritius, Morocco, Nigeria, South Africa, and Tunisia. In light of these findings, the policy implications are that African governments need to be conscientised on the benefits of financial market liberalisation and development. An open economy, complemented by adequate infrastructural and financial market development, plus appropriate regulation would play a significant role in attracting the type of international capital flow desired by the African host country’s level of economic development, without the concern of depleting other non-renewable natural resources.
Thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in the Faculty of Commerce, Law and Management, Wits Business School at the University of Witwatersrand, Johannesburg 2016
Keywords: Investments, Foreign--Africa; Economic development--Africa; Capital market--Africa